2020
DOI: 10.3168/jds.2019-17353
|View full text |Cite
|
Sign up to set email alerts
|

Regioisomeric and enantiomeric analysis of primary triglycerides in human milk by silver ion and chiral HPLC atmospheric pressure chemical ionization-MS

Abstract: Triglycerides (TG) not only provide energy for infants but have important physiological functions. Understanding the composition and structure of TG in human milk is conducive to the development of infant formulas. In this study, TG species in human milk from 3 provincial capitals (Zhengzhou, Wuhan, and Harbin) in different regions of China were determined through C18 HPLC electrospray ionization tandem mass spectrometry (MS). The results showed that in human milk from these 3 regions, oleoyl-palmitoyl-linoleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…The ratio of OPO vs. OOP is not equal in biological materials. While OPO is the dominant isomer in human milk (75–93%), the proportion of OPO is much lower (<60%) in bovine milk [ 9 , 10 , 11 , 12 ]. Being the most important commercial milk worldwide, bovine milk is used as a popular food ingredient, a common infant formula ingredient, as well as directly consumed as staple drink.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ratio of OPO vs. OOP is not equal in biological materials. While OPO is the dominant isomer in human milk (75–93%), the proportion of OPO is much lower (<60%) in bovine milk [ 9 , 10 , 11 , 12 ]. Being the most important commercial milk worldwide, bovine milk is used as a popular food ingredient, a common infant formula ingredient, as well as directly consumed as staple drink.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kalo et al [ 16 ] reported that normal-phase HPLC was able to separate AAB/ABA regioisomers (i.e., TAGs containing two types of FAs) with one or two short acyl (C4 or C6) chain, whereas most reversed-phase columns can only resolve regioisomers containing one double bond (DB), such as POP and PPO pair, but are unable to separate OPO/OOP pair, which contain two DBs [ 17 ]. Until now, only Ag + -HPLC-ELSD, in combination with a reversed-phase LC pre-fractioning in most cases, have been used successfully for the separation and quantitation of OPO/OOP in human milk and infant formula samples [ 10 , 12 , 18 ]. A simpler and a higher throughput method is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the share of the low-/mediate-molecular-weight TAGs was higher than that in mature milk ( 8 , 9 ). In addition, the differences of the TAGs of human milk collected from different cities were also found by several groups ( 9 11 ). It is common knowledge that the infants were recommended to provide human milk in the first 6 months of lactation; therefore, the composition of human milk during this period will provide more comprehensive information for designing of infant formula.…”
Section: Introductionmentioning
confidence: 73%
“… a B, butanoic acid; Ca, capric acid; La, lauric acid; M, myristic acid; Pe, pentadecanoic acid; P, palmitic acid; Po, palmitoleic acid; S, stearic acid; O, oleic acid; L, linoleic acid; Ln, linolenic acid; A, arachidic acid; E, Eicosenoic acid; B′, Behenic acid; –, unknown . b References for each country: Spain: Pons et al ( 15 ); Morera et al ( 4 ); Isabel Ten-Doménech et al ( 14 ); Denmark: Zou et al ( 5 ); America: Kim et al ( 16 ); China (previous studies): Tu et al ( 10 ); Yuan et al ( 9 ); Chen et al ( 11 ). Finland: Fabritius et al ( 17 ) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation